2008
DOI: 10.1093/occmed/kqn047
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of work-related musculoskeletal disorders in Brazilian hairdressers

Abstract: Occupational risk factors associated with the development of WRMDs in hairdressers are related to biomechanical, organizational and psychosocial work factors. The high prevalence of WRMDs found highlights the importance of disseminating recommendations for prevention of symptoms with regards to the provision of suitable furniture, equipment and work tools, environmental conditions, size of workplace, work organization and psychosocial work factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
53
3
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 7 publications
15
53
3
8
Order By: Relevance
“…In Brazil, according to the data from the Social Welfare Ministry, the WMSDs accounted for 52.8% of occupational diseases registered in 2001, 55.3% in 2002 and 50.1% in 2003. It has also been reported in Brazil that the most frequently affected body parts amongst hairdressers include the shoulder, the neck and back [6]. Mussi and Gouveia [6] reported that the prevalence of the WMSDs among hairdressers in Brazil was as high as 71%.…”
Section: Questionnaire Designmentioning
confidence: 96%
See 1 more Smart Citation
“…In Brazil, according to the data from the Social Welfare Ministry, the WMSDs accounted for 52.8% of occupational diseases registered in 2001, 55.3% in 2002 and 50.1% in 2003. It has also been reported in Brazil that the most frequently affected body parts amongst hairdressers include the shoulder, the neck and back [6]. Mussi and Gouveia [6] reported that the prevalence of the WMSDs among hairdressers in Brazil was as high as 71%.…”
Section: Questionnaire Designmentioning
confidence: 96%
“…Hairdressers are exposed to a variety of hazards in the workplace. These include chemical agents (products for hair), physical agents (noise, temperature) and ergonomic hazards (inappropriate posture during work and long working hours without breaks) [6]. In Brazil, according to the data from the Social Welfare Ministry, the WMSDs accounted for 52.8% of occupational diseases registered in 2001, 55.3% in 2002 and 50.1% in 2003.…”
Section: Questionnaire Designmentioning
confidence: 99%
“…This preference to conduct studies in organized industrial sectors and professions may not be peculiar to Nigerian scholars alone. Globally, prevalence studies on WMSDs among the self employed seem to be relegated to the background, apart from few on hair dressers [17][18][19]. Based on the aforementioned statements and the specific work activities of sewing machine operators, as well as dearth of literature on WMSDs on this population in Nigeria; this study was designed to determine the prevalence of WMSDs in sewing machine operators, the most frequently affected body parts, risk factors and coping strategies for WMSDs among self employed sewing machine operators in Maiduguri, Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Na hora do almoço e aos fins-de-semana, dado o maior número de clientes, a situação piora ainda mais 5 . Assim, fica mais provável o surgimento/ agravamento das LMEs 5,36 .…”
Section: Alterações Ergonómicasunclassified
“…Neste setor, por vezes, existe algum desconforto térmico 4,13,36 ; potenciado no verão e pelos secadores 4 .…”
Section: Desconforto Térmicounclassified